Perubahan Perkembangan Dalam Hukum Perdata Modern - Abdurrahman Konoras (IAIN Manado, 2017)
Changes in legal development occur because the law and society are dynamic. Changes in the private law have implications for the strengthening of internal control functions that replace external control functions. Developmental changes in the modern private law are closely related to the changing societies and ruling regimes, which strengthen the role and participation of the people on the one hand, and the diminishing role of the state on the other is inseparable from modernization and democratization within the state and society itself. The contract law, labor law, and consumer protection law are subject to changes arising from the strengthening of internal control functions that replace external control functions.